2021
DOI: 10.1111/brv.12806
|View full text |Cite
|
Sign up to set email alerts
|

The complex role of microbial metabolic activity in fossilization

Abstract: Bacteria play an important role in the fossilization of soft tissues; their metabolic activities drive the destruction of the tissues and also strongly influence mineralization. Some environmental conditions, such as anoxia, cold temperatures, and high salinity, are considered widely to promote fossilization by modulating bacterial activity. However, bacteria are extremely diverse, and have developed metabolic adaptations to a wide range of stressful conditions. Therefore, the influence of the environment on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 249 publications
(435 reference statements)
0
28
0
Order By: Relevance
“…Mineral precipitation is often an important step in the preservation of soft bodied organisms 82 . In all experiments, the precipitation of calcite crystals was detected at the inner side of the crayfish carapaces, though to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral precipitation is often an important step in the preservation of soft bodied organisms 82 . In all experiments, the precipitation of calcite crystals was detected at the inner side of the crayfish carapaces, though to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…Ediacara-style fossilization is not only distinctive of Ediacara Biota macroorganisms but also of microbial mats and biofilms or “matgrounds” that carpeted the Ediacaran seafloor and are similarly recorded as a variety of moldic textures, known as textured organic surfaces (TOS), in Ediacara fossil assemblages 28 . The characteristic spatial and ecological association of Ediacara macrofossils and microbial mat and biofilm textures across a wide range of Ediacara-style fossil deposits 29 31 has led to the suggestion that matgrounds, in addition to fostering the habitability of the Ediacara seafloor 32 39 and shaping the ecology of Ediacara communities 28 , 40 42 , may have also played a critical role in their fossilization 5 , 43 49 . Previous work has highlighted that bacteria may readily undergo silicification via Bitter Springs-style fossilization (i.e., permineralization of filamentous and coccoid microorganisms in cherts 50 – 53 ).…”
Section: Introductionmentioning
confidence: 99%
“…All the above damage to membrane, DNA, DNA gyrase, and antioxidant defense system would bring a devastating disaster for bacteria and induce metabolic inactivation. Metabolically active cells can reduce the redox indicator to pink fluorescent resofurin from blue Alamar Blue in the presence of functional enzymes. Hence, the fluorescent spectrum was applied to assess the effects of ATQ 17a on bacterial metabolic activity. The results in Figure S14 revealed that the metabolic activity of P. A. evidently declined with enhancing content of compound 17a .…”
Section: Results and Discussionmentioning
confidence: 99%